Relative Time Compression for Slow-Motion Stimuli through Rapid Recalibration - Kashiwakura, Saya; Motoyoshi, Isamu (Frontiers in Psychology, 2017)
A number of psychophysical studies have shown that moving stimuli appear to last longer than static stimuli. Here, we report that the perceived duration for slow moving stimuli can be shorter than for static stimuli under specific circumstances. Observers were tested using natural movies presented at various speeds (0.0x = static, 0.25x = slow, or 1.9x = fast, relative to original speed) and indicated whether test duration was perceived as longer or shorter than comparison movies presented at their original speed. While fast movies were perceived as longer than slow and static movies (in accordance with previous studies), we found that slow movies were perceived as shorter (i.e., time compressed) compared to static images. Similar results were obtained for artificial stimuli consisting of drifting gratings. However, time compression for slow stimuli disappeared if comparison stimuli were replaced by a white static disk that removed repetitive exposures to moving stimuli. Results suggest that duration estimation is modulated by contextual effects induced by the specific diet – or distribution – of prior visual stimuli to which observers are exposed. A simple model, which includes a rapid recalibration of human time estimation via adaptation to preceding stimuli, succeeds in reproducing our experimental data.